Chronological emergence of a class a carbapenemase-producing Enterobacter aerogenes in Taiwan - Zheng-Yi Huang; Jun-Ren Sun; Sheng-Ting Hsu; Ching-Mei Yu; Cherng-Lih Perng; Tzong-Shi Chiueh (Journal of Medical Sciences, 2014)
This study reports the case of a 77-year-old, long-term, bedridden patient, with a nosocomial wound infection caused by a multidrug-resistant strain of Enterobacter aerogenes (E. aerogense). The isolate produced an Ambler-class A carbapenemase, which was demonstrated by the Modified Hodge test (MHT) and a confirmatory inhibition test. However, no known carbapenemase genes were discovered in this isolate by polymerase chain reactions (PCRs) with specific primers. New carbapenemase or other resistant mechanisms could be explored from the isolate of carbapenem-resistant E. aerogense, according to the revised criteria (CLSI, 2012).